The relevance of kalikrein-kinin system via activation of B2 receptor in LPS-induced fever in rats. (November 2017) - Soares, Denis de Melo; Santos, Danielle R.; Rummel, Christoph; Ott, Daniela; Melo, Míriam C.C.; Roth, Joachim; Calixto, João B.; Souza, Glória E.P.
Abstract: Purpose: This study evaluated the involvement of endogenous kallikrein-kinin system and the bradykinin (BK) B1 and B2 receptors on LPS- induced fever and the POA cells involved in this response. Material and methods: Male Wistar rats received either i.v. (1 mg/kg), i.c.v. (20 nmol) or i.h. (2 nmol) injections of icatibant (B2 receptor antagonist) 30 or 60 min, respectively, before the stimuli. DALBK (B1 receptor antagonist) was given either 15min before BK (i.c.v.) or 30 min before LPS (i.v.). Captopril (5 mg/kg, sc., ) was given 1 h prior LPS or BK. Concentrations of BK and total kininogenon CSF, plasma and tissue kallikrein were evaluated. Rectal temperatures (rT) were assessed by telethermometry. Ca ++ signaling in POA cells was performed in rat pup brain tissue microcultures. Results: Icatibant reduced LPS fever while, captopril exacerbated that response, an effect abolished by icatibant. Icatibant (i.h.) reduced fever to BK (i.h.) but not that induced by LPS (i.v.). BK increased intracellular calcium concentration in neurons and astrocytes. LPS increased levels of bradykinin, tissue kallikrein and total kininogen. BK (i.c.v.) increased rT and decreased tail skin temperature. Captopril potentiated BK-induced fever an effect abolished by icatibant. DALBK reduced the fever induced by BK. BK (i.c.v.) increased the CSF PGE2 concentration. Effect abolished by indomethacin (i.p.). Conclusions: LPS activates endogenous kalikrein-kinin system leading to production of BK, which by acting on B2 -receptors of POA cells causes prostaglandin synthesis that in turn produces fever. Thus, a kinin B2 -receptor antagonist that enters into the brain could constitute a new and interesting strategy to treat fever. Highlights: Role of kininergic system in LPS-induced fever in rats. LPS-induced kalikrein-kinin system activation results in B2 -receptors in POA cells. Both POA cells activation and rats fever occurs after BK B2 -receptors stimulation.